Complicity, performance, and the 'doing' of sports coaching: An ethnomethodological study of work. Issue 3 (May 2020) - Corsby, Charles L.T.; Jones, Robyn L.
Recent attempts to 'decode' the everyday actions of coaches have furthered the case for sports coaching as a detailed site of 'work'. Adhering to Harold Garfinkel's ethnomethodological project, the aim of this article is to deconstruct contextual actors' interactions, paying specific attention to the conditions under which such behaviours occur. The article thus explores the dominant taken-for-granted social rules evident at Bayside Rovers Football F.C. (pseudonym), a semi-professional football club. A 10-month ethnomethodologically informed ethnography was used to observe, participate in and describe the Club's everyday practices. The findings comprise two principal 'codes' through which the work of the Club was manifest: 'to play well' and 'fitting-in'. In turn, Garfinkel's writings are used as a 'respecification' of some fundamental aspects of coaches' 'unnoticed' work and the social rules that guide them. The broader value of this article not only lies in its detailed presentation of a relatively underappreciated work context, but that the fine-grain analysis offered allows insightful abstraction to other more conventional forms of work, thus contributing to the broader interpretive project.